ON THE MARKETING RESEARCH OF CONSUMER PRICES AND INFLATION PROCESS - N. Dotchviri T, Todua (British Journal of Marketing Studies, 2015)
Marketing information is used by financial and insurance institutions, business enterprises and companies for planning, control, monitoring and forecasting purposes in business. One of the problems is the detection and investigation of factors, which influence the behavior of consumers. Such a basic factor is, for instance, the consumer prices index. The significance of this factor periodically changes and depends on the values of main indexes of economy such as export, import, taxes, labor force, unemployment, inflation level, etc., and also on the behavior of consumers, their taste, living standard and style. For the marketing research of this dependence it is necessary to construct mathematical models of the evolution of consumer prices. In the paper, a new auto regression model with disturbances is constructed for consumer prices. The model includes monetary aggregate amount and control function. A new formula is derived for the solution of an equation for the consumer prices index, which can be used in forecasting the inflation process. Using the data on the consumer prices index in Georgia, a numerical example is given, which illustrates the estimates of the coefficients of the constructed model and the inflation process forecast.